Spirituality and Mysticism: Some Historical Resources - Marquis, Christine Luckritz (Interpretation, 2023)
This article explores the growing interest in spirituality and mysticism, even as mainline churches lose members. It argues that attention to historical exempla from Christian origins to the medieval era offer fresh fonts of exploration for those western Christians seeking to retell the story of Christianity in an increasingly anxious and skeptical world.